(untitled) (Journal of Forest and Livelihood, 2024)
Despite changes in forestry policies to allow local communities to take control over national forests, efforts in facilitating devolution of power fail to recognize the ‘rights’ of people instead of ‘mercy’ of the state. The author highlights some fundamental issues that are at the root of many felt problems such as inequity, passive management of forests, limited access of the poor and marginalized in decision-making. The author proposes that rights based approach that focuses on local rights and organizing people can bring change, and Civil Society can play a significant role in this regard.